2011
DOI: 10.1007/s13213-011-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus lehensis—an alkali-tolerant bacterium isolated from cassava starch wastewater: optimization of parameters for cyclodextrin glycosyltransferase production

Abstract: A Gram-positive, endospore-forming, alkalitolerant bacterial strain, designated CGII, was isolated from the wastewater of a cassava flour mill in the state of São Paulo, Brazil and submitted to phylogenetic studies and biochemical tests. The 16S rRNA gene sequence indicated the highest degree of genomic similarity with MLB2 strains of Bacillus lehensis (100%). A two-level central composite rotatable design was then employed to optimize the medium composition and culture conditions for the production of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
19
0
4
Order By: Relevance
“…Blanco [38] reported that lower values of dissolved oxygen and rate of agitation may limit the uptake of nutrients by the microorganisms (such as the nitrogen source and starch), decreasing the synthesis of CGTase. Advances in Chemical Engineering and Science activity, approximately 0.5 U/mL, was obtained at 400 rpm and 1 vvm.…”
Section: Resultsmentioning
confidence: 99%
“…Blanco [38] reported that lower values of dissolved oxygen and rate of agitation may limit the uptake of nutrients by the microorganisms (such as the nitrogen source and starch), decreasing the synthesis of CGTase. Advances in Chemical Engineering and Science activity, approximately 0.5 U/mL, was obtained at 400 rpm and 1 vvm.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus lehensis CGII was isolated from wastewater samples from a cassava flour mill in Brazil. This bacterium is filed under the accession number HQ399547 (Blanco et al 2012). The B. lehensis CGII strain was inoculated in an Erlenmeyer flask containing 100 ml of optimised growth medium (Blanco et al 2012) and incubated at 35 ± 1°C for 72 h on a rotary shaker (New Brunswick Scientific Co, Edison, USA) at 150 rpm with an initial pH of 9.2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, novel CGTase-producing strains have been identified for this purpose (Blanco et al 2012). The purification degree of commercial enzymes depends on the application (Wolfgang 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CD production involves starch catalysis by the enzyme cyclodextrin glycosyltransferase (CGTase), produced by bacteria of the genera Bacillus [4], Paenibacillus [5], Klebsiella [6] and Thermoanaerobacterium [7]. Enzyme stability during catalytic activity and the separation of the product from the reaction medium are important factors to address, when using CGTase for CD production.…”
Section: Introductionmentioning
confidence: 99%